Identification of novel non‐coding RNA‐based negative feedback regulating the expression of the oncogenic transcription factor GLI1. Issue 5 (22nd March 2014) - Villegas, Victoria E.; Rahman, Mohammed Ferdous-Ur; Fernandez-Barrena, Maite G.; Diao, Yumei; Liapi, Eleni; Sonkoly, Enikö; Ståhle, Mona; Pivarcsi, Andor; Annaratone, Laura; Sapino, Anna; Ramírez Clavijo, Sandra; Bürglin, Thomas R.; et al.
Abstract : Non‐coding RNAs are a complex class of nucleic acids, with growing evidence supporting regulatory roles in gene expression. Here we identify a non‐coding RNA located head‐to‐head with the gene encoding the Glioma‐associated oncogene 1 (GLI1), a transcriptional effector of multiple cancer‐associated signaling pathways. The expression of this three‐exon GLI1 antisense (GLI1AS) RNA in cancer cells was concordant with GLI1 levels. siRNAs knockdown of GLI1AS up‐regulated GLI1 and increased cellular proliferation and tumor growth in a xenograft model system. Conversely, GLI1AS overexpression decreased the levels of GLI1, its target genes PTCH1 and PTCH2, and cellular proliferation. Additionally, we demonstrate that GLI1 knockdown reduced GLI1AS, while GLI1 overexpression increased GLI1AS, supporting the role of GLI1AS as a target gene of the GLI1 transcription factor. Activation of TGFβ and Hedgehog signaling, two known regulators of GLI1 expression, conferred a concordant up‐regulation of GLI1 and GLI1AS in cancer cells. Finally, analysis of the mechanism underlying the interplay between GLI1 and GLI1AS indicates that the non‐coding RNA elicits a local alteration of chromatin structure by increasing the silencing mark H3K27me3 and decreasing the recruitment of RNA polymerase II to this locus. Taken together, the data demonstrate the existence of a novel non‐coding RNA‐based negative feedback loop controlling GLI1 levels, thus expanding the repertoire of mechanisms regulating the expression of this oncogenic transcription factor. Highlights: A novel negative feedback loop on Hedgehog signaling is demonstrated. The mechanism involves a non‐coding RNA antisense to the GLI1 gene, GLI1AS. GLI1AS is shown to be a target gene of the GLI1 transcription factor. GLI1AS represses gene expression at the GLI1/GLI1AS locus. GLI1AS acts as an epigenetic modifier eliciting repressive chromatin marks.